A Comparative Study on the Photophysics and Photochemistry of Xanthene Dyes in the Presence of Polyamidoamine (PAMAM) Dendrimers. Issue 8 (19th February 2018) - Arbeloa, Ernesto Maximiliano; Previtali, Carlos Mario; Bertolotti, Sonia Graciela
Abstract: The photophysical and photochemical properties of the xanthene dyes Eosin Y, Erythrosin B, and Rose Bengal are evaluated in the presence of amino‐terminated polyamidoamine (PAMAM) dendrimers of relatively high generation (G3–G5) in alkaline aqueous solution. UV/Vis absorption and fluorescence spectra of the dyes show bathochromic shifts, which correlate with the size of the dendrimer. Binding constants ( K bind ) are calculated from absorption data. The resulting high K bind values indicate strong interactions between both molecules. Triplet–triplet absorption spectra of the dyes are recorded by laser flash photolysis, and a decrease in the triplet lifetimes is observed in the presence of dendrimers. At the same time, an increase in the absorption of the semireduced form of the dyes is observed. Rate constants for triplet quenching ( 3 k q ) and radical quantum yields ( Φ R ) are obtained. The results are explained by a very efficient electron‐transfer process from PAMAM to xanthene dyes for all of the dye/dendrimer couples that are evaluated. Abstract : The dye/dendrimer affair : The spectroscopic properties of xanthene dyes are modified in the presence of polyamidoamine (PAMAM) dendrimers through strong interactions between them. Transient absorption spectra are recorded by laser flash photolysis to show that electron transfer from PAMAM to xanthene dyes is a highly favored process (see figure).